Crystal structure of [{(η5-C5Me5)Fe(CO)2In(C6H2But 3-2,4,6)}2(μ-F)]+(BF4)-·3CH2Cl2 - Coombs, N; Watkin, D; Aldridge, S (2008)

(untitled)
The crystal structure of [{(η5-C5Me5)Fe(CO)2In(C6H2But3-2,4,6)}2(μ-F)]+(BF4)-·3CH2Cl2 was obtained, revealing the following properties: triclinic, space group P1 with a = 13.9482(2), b = 14.7621(2), c = 18.9520(2)Å, α = 104.9195(6), β = 93.6985(7), γ = 97.1409(5)°, Z = 2, R = 0.059 and wR2 = 0.133 for all 19611 unique reflections. The In-F-In bridging unit is characterized by In-F distances of 2.1674(18) and 2.1637(18)Å and by an In-F-In angle of 171.28(11)°; each indium centre is planar three-coordinate (∑angles at indium = 360°, within the standard 3σ limit, in each case) with In-Fe distances of 2.4740(5) and 2.4760(5)Å and Fe-In-Cipso angles of 153.75(8) and 154.79(9)°. 2008 © The Japan Society for Analytical Chemistry.